2020
DOI: 10.1111/1365-2435.13680
|View full text |Cite
|
Sign up to set email alerts
|

Relative reproductive phenology and synchrony affect neonate survival in a nonprecocial ungulate

Abstract: 1. Degree of reproductive synchronization in prey is hypothesized as a predator defense strategy reducing prey risk via predator satiation or predator avoidance. Species with precocial young, especially those exposed to specialist predators, should be highly synchronous to satiate predators (predator satiation hypothesis), | 2537 Functional Ecology MICHEL Et aL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 102 publications
(146 reference statements)
0
18
0
Order By: Relevance
“…Interestingly, the synchrony and phenology of ungulate reproduction is governed by resource availability (Sinclair et al 2000, Stoner et al 2016) and relative birthing synchrony and phenology affect neonate survival (Michel et al 2020). Given that our data demonstrate that fire timing regulates the timing of resource pulses, the anthropogenic mismatch in fire phenology could invoke strong selective pressure on the timing of ungulate reproduction if birth timing is a heritable trait and individuals not born during the fire-induced resource pulse do not subsequently successfully reproduce.…”
Section: Discussionmentioning
confidence: 77%
“…Interestingly, the synchrony and phenology of ungulate reproduction is governed by resource availability (Sinclair et al 2000, Stoner et al 2016) and relative birthing synchrony and phenology affect neonate survival (Michel et al 2020). Given that our data demonstrate that fire timing regulates the timing of resource pulses, the anthropogenic mismatch in fire phenology could invoke strong selective pressure on the timing of ungulate reproduction if birth timing is a heritable trait and individuals not born during the fire-induced resource pulse do not subsequently successfully reproduce.…”
Section: Discussionmentioning
confidence: 77%
“…We also predicted survival would increase with increased birth mass (Cook et al, 2004;Lomas & Bender, 2007;Shuman et al, 2017), age (Grovenburg et al, 2011;Nelson & Woolf, 1987;Rohm et al, 2007), canopy cover (Rohm et al, 2007;Sternhagen, 2015), and increased distance from the nearest road (Rost & Bailey, 1979;Stankowich, 2008). We predicted that survival would decrease with delayed birth dates (Plard et al, 2015, Michel, Strickland, et al, 2020, increased precipitation (Dion et al, 2020); Warbington et al, 2017, and increased distance from water (Adams & Hayes, 2008;Ditchkoff, 2011;Long et al, 2009). Finally, we predicted survival would be lower for females than for males (Shuman et al, 2017).…”
Section: Introductionmentioning
confidence: 77%
“…Additionally, although forested cover only comprised a small percentage of cover types in our study relative to grasslands and croplands, it may provide an important feature in helping neonates seek refuge from precipitation events, which can lead to hypothermia and subsequent death in neonates (Grovenburg et al, 2010(Grovenburg et al, , 2012Linnell et al, 1995;Warbington et al, 2017). Other cover types likely provide cover from precipitation and other weather events as neonates tend to select bed sites with an increased understory in grassland landscapes (Grovenburg et al, 2010;Michel, Strickland, et al, 2020). However, we could not attribute any mortalities directly to hypothermia, though we cannot discount the potential for hypothermic neonates being more sus- Our top model describing 6-month survival was S(Canopy + Precip2), which supported our prediction that percent canopy cover would positively affect survival while total precipitation would negatively affect juvenile survival.…”
Section: Discussionmentioning
confidence: 96%
“…Some research investigating glucocorticoid stress hormones studying ungulates reported similar patterns (Creel et al, 2009 ; Le Saout et al, 2016 ; Pecorella et al, 2016 ; Périquet et al, 2017 ; but see Zwijacz‐Kozica et al, 2013 ), but further investigation on ungulate hormonal response to predation and its fitness consequences are needed. In fact, predation has been related to decreased fecundity in hartebeest (Ng’weno et al, 2017 ) and white‐tailed deer (Cherry, Morgan, et al, 2016 , but see Michel et al, 2020 ) and contrasting results have been reported in elk (Creel et al, 2011 ; Middleton et al, 2013 ). Predator‐induced stress and selection of low‐quality forage to avoid predation have been suggested to cause decreased fecundity (Christianson & Creel, 2010 ; Ng’weno et al, 2017 ), but the specific pathways through which predation indirectly affect individual fitness still have to be defined.…”
Section: Resultsmentioning
confidence: 99%